The Role of the Surgeon in Primary Immune Thrombocytopenia: Case Report - Sanchez, Olga Nidia Montero; Valerio, María Gabriela Pesqueira; Manrique, Antonio Camacho; García, Carlos Lizcano; Garza, Jessica Torres; Cantú, Luis Alfonso Morales (British Journal of Healthcare and Medical Research, 2024)
Idiopathic thrombocytopenic purpura (ITP) is important as it is one of the most common thrombocytopenias in adults. Despite their medical treatment, there is a percentage of refractory patients who persist with severe hemorrhages, requiring splenectomy; this is where the surgeon becomes involved in this condition. The objective of this work is to present our experience with this disease and laparoscopic splenectomy in the general surgery service of the General Hospital of Saltillo, Coahuila, Mexico. We present the case of a 40-year-old male with a diagnosis of ITP since he was 28 years old, who for the last 12 years presented recurrent symptoms of severe hemorrhagic events with partial and temporary improvement of the condition despite aggressive pharmacological treatment. We were requested to consult the general surgery service due to therapeutic failure of pharmacological treatment, and a protocol for laparoscopic splenectomy was initiated. The patient progressed adequately and was discharged after the procedure with follow-up by outpatient clinic with a biopsy negative for malignancy.